Synthesis and Biological Evaluation of New Substituted 2-Mercaptobenzimidazole Derivatives as Anticancer and Anti-Inflammatory Agents - Pathan, Abjal; Deshmukh, Suparna R.; Farooqui, Mazahar (Asian Journal of Chemistry, 2026)
A series of fourteen 2-mercaptobenzimidazole derivatives (B1-B14) bearing a 6-chloro-5-(2,4-dichlorophenoxy) substituent was synthesized through S-alkylation of the corresponding benzimidazole-2-thiol. The derivatives were obtained in 75-85% yields and characterized by FTIR, 1H NMR, 13C NMR and mass spectrometry. Their biological potential was investigated through in vitro protein-denaturation and MTT assays. The protein-denaturation assay revealed concentration-dependent anti-inflammatory activity across the tested derivatives. Compounds B7 and B12 exhibited the strongest inhibition, followed by compounds B11 and B14, while B4, B6, B10 and B13 displayed moderate activity. At 100 µg/mL, all evaluated derivatives showed appreciable inhibition of protein denaturation, although the reference drug remained more active. In the MTT assay against MCF-7 breast cancer cells, compounds B6 and B14 exhibited the strongest concentration-dependent cytotoxic responses among the synthesized derivatives over 20-100 µg/mL. The findings identify compounds B7 and B12 as promising anti-inflammatory candidates and compounds B6 and B14 as potential antiproliferative leads, providing a basis for further mechanistic and pharmacological investigation.